PENGARUH KEPRIBADIAN TANGGUH (HARDINESS) TERHADAP RESILIENSI NARAPIDANA NARKOTIKA DI LEMBAGA PEMASYARAKATAN KELAS IIB LUBUK PAKAM - Siahaan, Maria Magdalena; Wibowo, Padmono (Universitas Nusa Cendana, 2024)
This study aims to determine the effect of a hardiness personality on the resilience of narcotics crime convicts at the Class IIB Lubuk Pakam Correctional Institution. This study uses quantitative research methods with non-probability sample techniques of as many as 83 respondents. The data analysis technique used in this study is through descriptive analysis test, simple linear regression test, significance test, and determination test which is processed using IBM SPSS software version 25. The research method used in this study uses statistical data analysis involving the t-test, with the results showing a positive and significant influence between hardiness personality and resilience of narcotics crime convicts at Class IIB Correctional Institution Lubuk Pakam. These results provide a better understanding of the importance of developing psychological intervention and rehabilitation programs that consider the resilient personality factor in improving the resilience of prisoners of narcotics crimes at the Class IIB Lubuk Pakam Correctional Institution. Keywords: Hardiness; Drug Offenders; Resilience